2022
DOI: 10.1038/s41598-022-14118-9
|View full text |Cite
|
Sign up to set email alerts
|

Mobile phones are hazardous microbial platforms warranting robust public health and biosecurity protocols

Abstract: Advancements in technology and communication have revolutionised the twenty-first century with the introduction of mobile phones and smartphones. These phones are known to be platforms harbouring microbes with recent research shedding light on the abundance and broad spectrum of organisms they harbour. Mobile phone use in the community and in professional sectors including health care settings is a potential source of microbial dissemination. To identify the diversity of microbial genetic signature present on … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
17
0
3

Year Published

2022
2022
2025
2025

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 15 publications
(20 citation statements)
references
References 16 publications
0
17
0
3
Order By: Relevance
“…can survive to passage through the gut in healthy adults and possibly generate further spread via wastewater (28, 29). Our observation raises the question of whether patients colonized with C. auris on the skin are also colonized in the gut and whether some human communities may harbor the previously unknown reservoirs of C. auris (30, 31). More studies of healthy people are needed to understand the prevalence of C. auris in the community (32).…”
Section: Discussionmentioning
confidence: 93%
“…can survive to passage through the gut in healthy adults and possibly generate further spread via wastewater (28, 29). Our observation raises the question of whether patients colonized with C. auris on the skin are also colonized in the gut and whether some human communities may harbor the previously unknown reservoirs of C. auris (30, 31). More studies of healthy people are needed to understand the prevalence of C. auris in the community (32).…”
Section: Discussionmentioning
confidence: 93%
“…[ 18 ] Matthew and Rania also found that mobile phones that are not decontaminated may pose serious risks for public health and biosecurity. [ 19 ] Nightingale et al . also concluded that bacterial mask contamination was not associated with health-care profession or exposure and did not increase after 6 h of mask wearing in our nursing home setting.…”
Section: Discussionmentioning
confidence: 99%
“…90 random samples were collected 30 samples from the cover of the mobile phone and30 samples from the finger of its users for 15 females and 15 males ,tow samples for each person of different ages, residence, occupation, especially the pioneers of the Department of Life Sciences, College of Science, University of Mosul, the quality of the device, the number of hours of use, the region, the last time the hands were washed and the user's hand is right or left. North, the samples were taken by wearing sterile gloves and change it frequently to avoid fungal infection [12] and passing the cotton swab mixed with saline in a planned manner [13] on each of the mobile cover and the most used finger. The samples were planted in Petri dishes containing PDA and SDA medium and incubated at 28C° for 3 days, and then the results were taken at a rate of 7,5,3 days.…”
Section: Fungi Isolationmentioning
confidence: 99%